Determining the Water Quality from Selected Underground Water Springs and Other Selected Sources of Water Around Kabale Municipality. - Kemigisha, Angella (Kabale University, 2024)
This study investigated the water quality of water from selected underground water springs and other selected sources of water (Rwabakazi, Nyakiharo well, Kirigime well, and tap water) around Kabale municipality. The study was conducted in Kabale Municipality located in Kabale district, southwestern Uganda. The study principally determined the quality of water from underground water springs, wells, tap water from Kirigime, Nyakiharo, Nyakambu, and Rwamukundi, and River Rwabakazi. This study aimed at helping residents within the sampled sites to identify which of the water is suitable for human consumption. This involved the determination of the physicochemical parameters (pH, chloride ion concentration, and total hardness) of water obtained from the selected domestic water sources by quantitative analysis which involved titration except for water pH which was determined using a pH meter at the location. The results showed that Tap water with a pH of 6.7 on average, which was within the recommended range of 6.5-8.5 by WHO, a chloride concentration of 245ppm which was also in the range of 200-300ppm and a total hardness of 100. Hence showed that tap water was suitable for domestic use. While other sources diverted from the recommended values by WHO, River Rwabakazi had the largest diversity from the recommended values by WHO thus its water was not suitable for domestic use. It was recommended that agricultural activities around water sources be regulated to avoid water contamination.